An Immunosuppressive Effect of Melanoma-derived Exosomes on NY-ESO-1 Antigen-specific Human CD8+ T Cells is Dependent on IL-10 and Independent of BRAFV600E Mutation in Melanoma Cell Lines. (2nd October 2020) - Shu, ShinLa; Matsuzaki, Junko; Want, Muzamil Y.; Conway, Alexis; Benjamin-Davalos, Shawna; Allen, Cheryl L.; Koroleva, Marina; Battaglia, Sebastiano; Odunsi, Adekunle; Minderman, Hans; Ernstoff, Marc S.
ABSTRACT: Exosomes, including human melanoma-derived exosomes (HMEX), are known to suppress the function of immune effector cells, which for HMEX has been associated with the surface presence of the immune checkpoint ligand PD-L1. This study investigated the relationship between the BRAF mutational status of melanoma cells and the inhibition of secreted HMEX exosomes on antigen-specific human T cells. Exosomes were isolated from two melanoma cell lines, 2183-Her4 and 888-mel, which are genetically wild-type BRAF WT and BRAF V600E, respectively. HMEX were isolated using a modified, size-exclusion chromatography (SEC) method shown to reduce co-isolation of non-exosome-associated cytokines compared to ultracentrifugation isolation. The immunoinhibitory effect of the exosomes was tested in vitro on patient-derived NY-ESO-1-specific CD8 + T cells challenged with NY-ESO-1 antigen. HMEX from both cell lines inhibited the immune response of antigen-specific T cells comparably, as evidenced by the reduction of IFN-γ and TNF-α in NY-ESO-1 tetramer-positive cells. This inhibition could be partially reversed by the presence of anti-PD-L1 and anti-IL-10 antibodies. IL-10 has been demonstrated to be a critical pathway for sustaining enhanced tumorigenesis in BRAF V600E mutant cells compared to BRAF WT melanoma cells. Thus, we demonstrate that HMEX inhibit antigen-specific T cell responses independent of the BRAF mutational status of the parent cells. In addition, PD-L1 and IL-10 contribute to the HMEX-mediated immunosuppression of antigen-specific human T cells. The inhibitory capacity of exosomes should be taken into consideration when developing therapies that are reliant upon the potency of customized, antigen-specific effector T cells.